Optimalisasi Tatakelola dan Pelayanan di Laboratorium Sebagai Penunjang Tridharma Perguruan Tinggi - Zulpadrianto, Zulpadrianto; zalnur, muhammad (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The laboratory is an academic support for educational institutions that are systematically managed for testing, calibration, and / or production activities on a limited scale in the context of implementing education, research, and community service. In order to function optimally a laboratory needs to be evaluated periodically. This research was conducted in the context of evaluating service to users in six aspects, namely: 1. Tangibles aspects (Laboratory Facilities, Equipment Completeness),2. Reliability aspects (reliability of teaching staff, Academic staff),3. Responsiveness Aspects (Responsiveness / K3 availability in the laboratory)4. Empathy Aspects (Understanding of the interests of visitors) and 5. Aspects of Assurance (treatment of users) and 6. Aspects of Innovation in governance and services. The method used is a mixture of quantitative and qualitative methods using questionnaire instruments, interviews, and document studies. The results showed that the Tangibles Aspect, Reliability, Responsiveness, Empathy and Assurance as well as the Innovation Aspect were in a fairly good condition.